Impact of Fiscal Decentralization Policy on Regional Fiscal Independence in Indonesia - Pabayo, Antonius Sasana Talino (Journal of Local Government Issues, 2025)
This study aims to analyse the impact of fiscal decentralisation policies on regional fiscal independence in Indonesia. Using a qualitative descriptive method and meta-analysis technique, this study reviewed 30 samples of related literature. The results show that fiscal decentralisation has mixed impacts: 15 studies showed a positive influence on fiscal independence through the delegation of authority to manage local revenue and expenditure, while 10 studies reported negative impacts, including high dependence on central transfers and corrupt practices. In addition, 5 studies revealed mixed results. The positive impact of decentralization can be seen from the devolution of local taxes and levies as well as central transfers such as General Allocation Fund (DAU), Specific Allocation Fund (DAK), and Revenue Sharing Fund (DBH), which help regions tap into local economic potential and increase local fiscal independence. However, limited management of revenue sources, weak supervision, and central dominance in budget allocation are major challenges. The conclusion of this study shows that fiscal decentralisation still faces obstacles in realising full fiscal independence. Recommendations include strengthening local financial governance, reducing dependency on central transfers, and increasing local economic capacity through inclusive and democratic policies. Thus, fiscal decentralisation is expected to be an effective instrument to promote sustainable regional development.